Integration of Tiktok Learning Games (TLG) as a Learning Innovation to Improve Academic English Proficiency of English Education Students at Medan State University (International Journal of Education and Literature, 2025)
In the digital age, English Education students still face difficulties in developing Academic English Proficiency because classroom learning is still dominated by traditional methods that are less appealing to digital natives. This study aims to explore and evaluate the integration of TikTok Learning Games (TLG) as a gamification-based learning medium to improve EAP for students in the English Education Study Program at Medan State University. Using a qualitative approach with a limited Research and Development model, data was collected through open-ended questionnaires and digital observations on TikTok, then analyzed using thematic analysis. The results showed that after two weeks of implementing TLG, students experienced improvements in academic vocabulary, pronunciation, contextual understanding, learning motivation, and speaking confidence, with 80% of participants stating that learning felt more enjoyable and less boring. However, a small number of students did not show significant changes due to limited access to technology and inconsistent use. Overall, this study concludes that TLG is an effective and practical digital gamification strategy for improving English proficiency, and can be used as a reference for lecturers in developing social media-based learning innovations in higher education.